ESTUDIO DE FACTIBILIDAD PARA LA CREACIÓN DE UNA PLANTA DESHIDRATADORA SOLAR DE FRUTAS EN LA CIUDAD DE RIOBAMBA - Unach (2019)
Through the market study it was determined that people prefer as dried fruit pineapple, mango, banana and uvilla, there is also great acceptance of the product in presentations of 50g and that there is an unsatisfied demand of 60% of which the company will cover 3% for it requires processing 99.41 kg of fresh fruit a day. As part of the technical study was defined that to process 99.41 kg of fruit per day requires a plant of 106 m2, as to the facilities was found that the key equipment in the process is the solar dehydrator, two of these are required to meet daily production, also determined the human talent, equipment and tools, raw materials and inputs for production. The financial study determined that the total investment is $42960.15, the manufacturing cost of a 50 g container is $ 0.99, the selling price is $1.50 which means a profit of 52 %, the evaluation of the project showed a NPV of $ 63451.72, the IRR 69.85 %, TMAR 7.45 %, Profit/Cost is $1.44, the recovery period will be 1 year 1 month, the risk of the initial investment will be balanced based on the increase in production while maintaining the same price of introduction thus achieving entry into new markets.